Meaning Revealed: Grebeg Besar in Demak, Central Java - Muawanah, Siti (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2006)
This article examines a Javanese Muslim celebration known as Grebeg Besar, a celebration which maintains cultural heritage, disseminates Islam and raises the regional income of the people of Demak. Demak was established by Raden Fatah.6 According to Babad Tanah Jawa, Raden Fatah was a descendant of the last Majapahit king, Kertabhumi Brawijaya V, from a Chinese prince who was given to his favorite boy, a governor of Palembang, Arya Damar or Joko Dillah. Together with his younger brother, Raden Husen,e Raden Fatah went to Java to devote his life to the King Brawijaya V,10 by joining a ship of a trader. After landing on the coast of Java, these two brothers went their separate ways. Raden Husen continued his journey to Majapahit and became an Adipati of Terung, while Raden Fatah felt reluctant to serve a kafir (infidel) king and preferred to learn Islam under the tutelage of Sunan Ampel.DOI: 10.15408/sdi.v13i3.558